The Demand for Quality in Child Care - Blau, David M.; Hagy, Alison P. (Journal of Political Economy, 1998)
We estimate a model of demand for quality‐related attributes of child care: group size, staff/child ratio, and provider training. The model is estimated jointly with equations for mode, expenditure on and hours of care, and the mother's labor supply. The results show that a lower price of child care in a particular mode leads to substitution toward that mode and an increase in the use of paid child care. A decrease in the price of care causes an increase in hours of care demanded and a decrease in the demand for qualityrelated attributes. Income effects on demand for quality are small.